1970
DOI: 10.1071/ph700953
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Test of the Streamer Breakdown Criterion

Abstract: The filamentary spark channel, resulting from the electrical breakdown of a gas, generally forms in one of two ways. At voltages close to the minimum breakdown potential the spark channel has been shown to develop from the constriction of the diffuse glow discharge formed from the superposition of many generations of electron avalanches (Cavenor and Meyer 1969). At large overvoltages, however, single avalanches have been observed to develop into luminous conducting filaments, called streamers, which completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Our observations with conditioned electrodes are in general agreement with the Australian work (Cavenor andMeyer 1969, Cavenor 1970) who used conditioned electrodes in their experiments.…”
Section: Conditioned Electrodessupporting
confidence: 92%
See 1 more Smart Citation
“…Our observations with conditioned electrodes are in general agreement with the Australian work (Cavenor andMeyer 1969, Cavenor 1970) who used conditioned electrodes in their experiments.…”
Section: Conditioned Electrodessupporting
confidence: 92%
“…Recently Meyer and Lee (1971) have shown that the glow characteristics are independent of the source impedance. Cavenor (1970) has confirmed the existence of the glow phase at overvoltages up to 100% and a pressure of 500 Torr, and Cavenor and Meyer (1969) also showed that this diffuse glow subsequently constricts to a filamentary discharge which still shows a cathode dark space at the cathode and which causes a further drop in the gap voltage. There is a progressive increase in the current through the filament until, finally, a discontinuity at the cathode accompanied by the disappearance of the dark space leads to a sudden increase in luminosity and electrical conductivity and the gap voltage collapses to very low values.…”
Section: Introductionmentioning
confidence: 78%
“…terminology can be exemplified by the following claim by Cavenor [106]: 'The filamentary spark channel, resulting from the electrical breakdown of a gas, generally forms in one of two ways. At voltages close to the minimum breakdown potential the spark channel has been shown to develop from the constriction of the diffuse glow discharge formed from the superposition of many generations of electron avalanches.…”
mentioning
confidence: 99%
“…The development of spark discharges is known to proceed in several different ways, depending on the gas and its pressure, the discharge gap and electrode geometry, the external circuit and the magnitude of the overvoltage applied to the discharge gap (cf Haydon 1968, Craggs 1978. The role of overvoltage, for example, is regarded as important at gas pressures of several hundred Torr and under uniform field conditions (Cavenor andMeyer 1969, Kekez er aZ1970). At low overvoltage, under these conditions, the spark develops by the Townsend mechanism, and at high overvoltage, generally by the so-called streamer mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…At low overvoltage, under these conditions, the spark develops by the Townsend mechanism, and at high overvoltage, generally by the so-called streamer mechanism. This is not an exact rule however, and the Townsend mechanism has been observed to operate for overvoltages as high as 100% (Cavenor 1970). In this paper, we are more concerned with the later stages of development which follow the establishment of a diffuse glow discharge; this is a quasi-stable stage in the spark development which often follows the initial breakdown process.…”
Section: Introductionmentioning
confidence: 99%